2020
DOI: 10.1029/2019jd031372
|View full text |Cite
|
Sign up to set email alerts
|

A Decadal Climatology of Chemical, Physical, and Optical Properties of Ambient Smoke in the Western and Southeastern United States

Abstract: Biomass burning is a major source of summertime fine particulate matter in the United States, degrading air quality and affecting human health and climate. Fuels, burn conditions, and fire types vary across the United States, which may impact smoke composition and optical properties. We use the Hazard Mapping System to track smoke plumes for 10 years from 2008 to 2017, focusing on three U.S. regions: Southeast, Pacific West, and Southwest. Combining this geospatial data set with AErosol RObotic NETwork (AERONE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 77 publications
0
21
1
Order By: Relevance
“…The strong SO₄ 2− enhancement on BB days is noteworthy as Bian et al. (2020) previously showed that smoke in the southeast U.S. has a higher SO₄ 2− fraction than smoke over the western U.S. Furthermore, Bian et al.…”
Section: Resultsmentioning
confidence: 81%
“…The strong SO₄ 2− enhancement on BB days is noteworthy as Bian et al. (2020) previously showed that smoke in the southeast U.S. has a higher SO₄ 2− fraction than smoke over the western U.S. Furthermore, Bian et al.…”
Section: Resultsmentioning
confidence: 81%
“…Volume size distributions of smoke aerosol from Bian et al. ( 2020 ) indicate that <5% of PM 2.5 volume (and hence mass) exists in the diameter range of 1–2.5 µm, thus errors due to this assumption are <5%, smaller than the relative uncertainty from the concentration response function. Further, we assumed that the WE‐CAN HAPs to PM 1 ratios are representative of all US smoke plumes, but smoke HAPs concentrations may vary by fuel type (e.g., Gilman et al., 2015 ), burn conditions (Sekimoto et al., 2018 ), and smoke age (O’Dell et al., 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, in order to use these HAP to PM1 ratios with our krigged smoke PM2.5 estimates, we assumed the mass concentration of particles with diameters betweeen 1 µm and 2.5 µm was negligible. Volume size distributions of smoke aerosol from Bian et al (2020) indicate that <5% of PM2.5 volume (and hence mass) exists in the diameter range of 1-2.5 µm, thus errors…”
Section: Accepted Articlementioning
confidence: 99%
“…To compare HAPs to PM 2.5 ratios at Boulder Reservoir to those reported in O'Dell et al (2020), which are to PM 1 mass, we assume mass contribution from smoke particles with diameters between 1 and 2.5 µm is negligible. Volume size distributions (which are directly proportional to mass size distributions under constant particle density) from (Bian et al, 2020) indicate particles of diameter range 1-2.5 µm contribute <5% of total PM 2.5 volume in smoke. We find the distribution of benzene to PM 2.5 ratios during smoke impacted periods at Boulder Reservoir to be similar to those reported in O'Dell et al (2020); however, ratios of toluene and hexane to PM 2.5 at Boulder Reservoir are higher than O'Dell et al (2020).…”
Section: Hazardous Air Pollutantsmentioning
confidence: 99%